KOMUNIKASI ISLAM DAN FUNGSI KELUARGA PADA POLA ASUH KENABIAN UNTUK MENGUATKAN KETAHANAN KELUARGA - Miftahul Jannah; Muhammad Ali Najich (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study examines the integration of Islamic communication, family functions, and Prophetic Parenting as a strategy to strengthen the resilience of Muslim families in the digital era. This study uses the Systematic Literature Review (SLR) method, guided by PRISMA 2020, to analyze 70 scientific articles selected through identification, screening, feasibility assessment, and inclusion, and then analyzed using a thematic approach. The findings show that the digital age, characterized by information overload, high screen time, and social media fatigue, disrupts communication quality, emotional stability, and family functioning. Islamic communication based on qaulan sadidan, ma'rufan, layyinan, and maysuran significantly increases family interaction and emotional attachment, while reducing digital communication conflicts. The integration of these values into the family's religious, educational, affective, protective, social, and recreational functions strengthens cohesion, a sense of security, and spiritual internalization. Prophetic Parenting through habituation (ta'wid), wise counsel (maw'izah), and compassion (rahmah) has proven to be effective in forming an adaptive and harmonious family. Overall, families that practice Islamic communication within the framework of Prophetic Parenting show better ability to manage digital media, internalize Islamic values, and maintain emotional and spiritual balance.